Faktor Pendorong dan Penghambat Keberhasilan Kewirausahaan - Fitria Ghaida Nur Rahma; Annysa Gea Putri; Dinda Nurul Wahidiyah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Entrepreneurship is an ability that has a creative and innovative nature. This creative and innovative ability is used as the basis for an entrepreneur's intentions and tips for finding opportunities and improving the quality of life. Entrepreneurship has become a very important part in developing economic growth, innovation and competitiveness in various regions. Encouraging and inhibiting factors are important elements in the success of an entrepreneur which enable an entrepreneur to evaluate and improve the business he is running. The purpose of writing this article is so that readers can find out the driving factors and inhibiting factors of entrepreneurship to learn and understand before starting entrepreneurship. This research uses a qualitative method that emphasizes explanatory analysis of the factors driving and inhibiting entrepreneurial success. To get more information about the factors that encourage and inhibit entrepreneurial success. This research concentrates on providing an in-depth explanation of the components that are very important for achieving success in entrepreneurship. It is hoped that this research will increase our understanding of. In entrepreneurship, driving and inhibiting factors are important elements for an entrepreneur to be able to evaluate and improve the business he is running. Having a deep understanding of the elements that drive and hinder entrepreneurial success enables the development of more efficient plans to overcome challenges and exploit opportunities.